Pengaruh Pelanggaran Privasi Data Terhadap Keputusan Pembelian Pengguna Tokopedia Menggunakan Theory Of Planned Behavior (TPB) - Pakpahan, Farida Manin; Suratno, Tri; Lestari, Dewi (Fakultas Teknik Universitas Hamzanwadi, 2025)
The rapid growth of e-commerce in Indonesia, led by platforms like Tokopedia, has transformed consumer behavior while also raising serious data privacy concerns. The 2020 Tokopedia data breach, involving 91 million user records leaked on the dark web, highlighted the vulnerability of personal data and risks such as identity theft and online fraud. This study investigates the impact of privacy breaches on Tokopedia users’ purchasing decisions in Jambi City using a quantitative approach grounded in the Theory of Planned Behavior (TPB). The study examines the influence of perceived data security, risk perception, attitude, subjective norms, and perceived behavioral control on purchase intention and actual buying behavior. Data were collected from 240 respondents through a questionnaire and analyzed using PLS-SEM with SmartPLS 4.0. Findings reveal that perceived data security has a significant positive effect on purchase intention, while risk perception has a significant negative effect. However, attitude and subjective norms show no significant impact on purchase intention, and behavioral intention does not significantly affect actual purchasing behavior. These results suggest that after a privacy breach, consumers prioritize data security over social or personal factors. E-commerce platforms must enhance data protection and maintain transparent communication to rebuild and retain consumer trust.